Performance of Permeable Pavement to Filter Stormwater Runoff for Non-Potable Uses in Buildings - Thives, Liseane Padilha; Ghisi, Enedir; Longo, Gianfranco; Hammes, Gabriela; Belotto, Thiago (European Journal of Sustainable Development, 2023)
Permeable pavement benefits, besides stormwater runoff reduction and groundwater recharge, include stormwater harvesting. As an alternative to water resources scarcity, stormwater that reaches a permeable pavement could be filtered by the same pavement and then used for non-potable purposes in buildings. This work aims to evaluate some types of permeable pavements regarding their performance to remove pollutants from stormwater and decrease runoff. Analyses of infiltration capacity and pollutant concentrations were performed in four permeable pavement models with different types of permeable surface layer (porous asphalt mixture and porous interlocked concrete blocks). Then, the data were used to calculate the “stormwater credits” according to the Minnesota Stormwater Manual. The credits were calculated for volume of runoff, and concentrations of Total Suspended Solids (TSS) and Total Phosphorus (TP). As a result, the models proved adequate to decrease both stormwater runoff and TSS and TP concentrations. Moreover, models with the porous asphalt mixture as a surface layer were more efficient to reduce the concentration of pollutants. However, for the models evaluated in this work, additional treatment is recommended when stormwater harvested from permeable pavements is meant for non-potable uses in buildings. Keywords: buildings, stormwater, credits, non-potable uses.